Valor simbólico, turístico y económico de las festividades más representativas del distrito de Sinsicap para promover el desarrollo del turismo. - Escobar Natividad, Yeni Soledad (2018)
The present research work entitled Symbolic, tourist and economic value of the most representative festivities of the Sinsicap District to promote the development of tourism; It is aimed at determining which are the values that present the most representative festivities of the district. _x000D_ The variables that governed this research were three; the symbolic value, which is directed towards popular beliefs, the level of pride of the villager, historical events of the festivities, degree of identity, faith and devotion of the population towards their patron; the tourist value is focused on the categorization and hierarchy of the most representative festivities of the district as a tourist resource, gastronomy, pyrotechnics, dances and music typical of the place; in terms of economic value, it is oriented towards the cost of the bands of musicians and castles, the percentage of the profits on the part of the lodging houses, restaurants and transportation, as well as the approximate budget that is required for the realization of an employer's festivity such as that are celebrated in the district of Sinsicap. _x000D_ As a result of the investigation and according to the data presented as support for the variables symbolic value, tourism value and economic value, it is concluded that the most representative festivities of the Sinsicap District have the presence of the three types of values under study, to achieve in this way the development of tourism. _x000D_ For this research, the methods used were: The Historical Comparative method and the Synthetic Analytic, also the techniques used were: Direct Observation, the Survey, the Interview, Direct Observation - Participant and the Transfer Lastly, the instruments used were: Survey Questionnaire, Photographic Camera, Field Notebook, Interview Guide and Fact Sheets. _x000D_ To carry out this research it was required to have a sample of the entire population of the District of Sinsicap, for this we used the information of District Population of the PEA (Economically Active Population), where the population to be considered is 2 746 inhabitants for which the result of the sample is 246 inhabitants, with whom the research was developed.